Use of chest X-ray in the assessment of community acquired pneumonia in primary care - an intervention study - Anna B Moberg; Moa Kling; Jakob Paues; Sven Göran Fransson; Magnus Falk (Taylor & Francis Group, 2020)
Objectives The aim of this study was to explore if consequent use of chest X-ray (CXR), when the physician is not sure of the diagnosis of pneumonia after clinical examination and CRP-testing, favors a more restrictive prescribing of antibiotics. Design This was an intervention study conducted between September 2015 and December 2017. Setting Two intervention primary health care centers (PHCCs) and three control PHCCs in the southeast of Sweden. Intervention All patients were referred for CXR when the physician´s suspicion of pneumonia was 'unsure', or 'quite sure' after CRP-testing. Control units managed patients according to their usual routine after clinical examination and CRP-testing. Subjects A total of 104 patients were included in the intervention group and 81 patients in the control group. The inclusion criteria of the study were clinically suspected pneumonia in patients ≥18 years, with respiratory symptoms for more than 24 h. Main outcome measure: Antibiotic prescribing rate. Results In the intervention group, 85% were referred for CXR and 69% were prescribed antibiotics, as compared to 26% and 77% in the control group. The difference in antibiotic prescribing rate was not statistically significant, unadjusted OR 0.68 [0.35-1.3] and adjusted OR 1.1 [CI 0.43-3.0]. A total of 24% of patients with negative CXR were prescribed antibiotics. Conclusion This study could not prove that use of CXR when the physician was not sure of the diagnosis of pneumonia results in lowered antibiotic prescribing rate in primary care. In cases of negative findings on CXR the physicians do not seem to rely on the outcome when it comes to antibiotic prescribing.Key Points Routine use of chest X-ray when the clinical diagnosis of pneumonia is uncertain has not been proven to result in lowered antibiotic prescribing rate. Physicians do not fully rely on chest X-ray outcome and to some extent prescribe antibiotics even if negative, when community-acquired pneumonia is suspected. Chest X-ray is already used in one out of four cases in routine primary care of pneumonia patients in Sweden.